2018
DOI: 10.3389/fpls.2018.01425
|View full text |Cite
|
Sign up to set email alerts
|

Pesticidal Plant Extracts Improve Yield and Reduce Insect Pests on Legume Crops Without Harming Beneficial Arthropods

Abstract: In the fight against arthropod crop pests using plant secondary metabolites, most research has focussed on the identification of bioactive molecules. Several hundred candidate plant species and compounds are now known to have pesticidal properties against a range of arthropod pest species. Despite this growing body of research, few natural products are commercialized for pest management whilst on-farm use of existing botanically-based pesticides remains a small, but growing, component of crop protection practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
121
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 79 publications
8
121
0
3
Order By: Relevance
“…Table 1, illustrates the proportions of chemotypes by countries. The abundance in plant materials with chemotype 1 coincided with efficacy studies of T. vogelii on medicinal [10,13,21,30] and insecticidal properties of rotenoids [15][16][17]31] which revealed that rotenoids were the compounds most frequently found in T. vogelii sampled and are responsible for the plants' biological activity.…”
Section: Frequency Of T Vogelii Chemotypesmentioning
confidence: 65%
See 1 more Smart Citation
“…Table 1, illustrates the proportions of chemotypes by countries. The abundance in plant materials with chemotype 1 coincided with efficacy studies of T. vogelii on medicinal [10,13,21,30] and insecticidal properties of rotenoids [15][16][17]31] which revealed that rotenoids were the compounds most frequently found in T. vogelii sampled and are responsible for the plants' biological activity.…”
Section: Frequency Of T Vogelii Chemotypesmentioning
confidence: 65%
“…Specifically, research on T. vogelii reported medicinal properties such as anti-cancer activity [7][8][9] and efficacy as an ectoparasite treatment for domestic animals including poultry [10][11][12][13][14]. A number of studies have sought to validate the reported use of T. vogelii as a botanical insecticide under laboratory and field conditions and have reported its effectiveness for crop protection and reduced impacts on beneficial ecosystem services [15][16][17]. Likewise, Tephrosia is reported to have high biomass and is therefore important as a soil amendment and is compatible with food crops when intercropped in addition to its nitrogen fixing property [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these methods has yet delivered a viable option for effective control of FAW, hence the search for alternative approaches including those from plant extracts and their products. Some pesticidal plants and botanical insecticides are effective and their use could reduce reliance on synthetic insecticides since they have lower non-target impacts and could even boost growth [16][17][18][19]. Here we review existing research on plant extracts that have been evaluated for the management of FAW with the aim of identifying those with potential for use by small-scale farmers in Africa, or informing approaches to identifying and evaluating untested native African plant taxa since pesticidal plants are already used as crudely produced products among smallholder farming communities in Africa with notable success [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This means they may need more frequent application incurring greater costs in time. However, as they are non-persistent, they are potentially less damaging to the environment particularly non-target insects [17,18,99,101].…”
mentioning
confidence: 99%
See 1 more Smart Citation